Relationship of HER-2 Overexpression with Size and Stage of Tumor In Patients With Primary Breast Carcinoma (KYAMC Journal, 2025)
Background: Receptor study for carcinoma breast is now a common practice before neoadjuvant therapy. Human Epidermalgrowth factor Receptor 2 (HER2) overexpression acts as a predictive marker of tumor aggressiveness.Objective: To determine the association of HER-2 overexpression in relation to tumor size and stage of breast carcinoma.Materials and Methods: A cross sectional study was carried out in SSMC & Mitford Hospital from July 2008 to June 2010. 52patients with primary breast carcinoma were selected. Clinical features and histopathological findings were studied. Size, stageand overexpression to HER-2 receptor were the primary variables. Chi-square test, Mann Whitney test and Odds Ratio wereperformed for data analysis.Results: Out of 52 patients, 38.5% were 41 – 50 years of age, and nearly 60% of the patients were in the premenopausal state.Over half (51.9%) of the patients had a history of contraceptive use and 21.1% of the patients had a family history of breastcancer. Overexpression of HER-2 (56.3%) was found to be significantly associated with lymph node positivity (p = 0.005). 52.6%of the advanced stage (stage IIIa – stage IV) tumors had overexpression of HER-2. 57.1% of tumor ≥5cm exhibited overexpressionof HER-2 as opposed to only 16.7% of the tumor